CIRCULAR ECONOMY: A CONTRIBUTION TO THE SUSTAINABLE DEVELOPMENT: ECONOMIA CIRCULAR: UMA CONTRIBUIÇÃO PARA O DESENVOLVIMENTO DA SUSTENTABILIDADE - Tiossi, Dr. Fabiano Martin; Simon, Dr. Alexandre Tadeu; Milan, Willyan Wilson (Brazilian Journal of Production Engineering, 2019)
The aim of this study is to identify the effective contributions of Circular Economy to the development of Sustainability. With the practice of sustainable action by companies, positive results started to appear, but even with strategies for combat and prevention of problems coming from misuse of natural resources, these practices showed themselves insufficient to solve the problems of contemporaneity. This way, new discussions appear with the challenge to include innovative actions, which lead to sustainable development, minimizing the impacts caused by the results coming from linear economy. The Circular Economy appears as one of the best alternatives of contribution to the resoluteness of these several problems. The methodology used in this study was the systematic review of literature, having as the main source of research the base ISI Web of Science. By the results, it is evidenced that Sustainability and Circular Economy have in common the aim of approaching environmental, economic and social problems. However, it is also identified by scientific literature that Circular Economy presents new items that are not contemplated by Sustainability, emerging as a new support strategy to sustainable development, a tool that came to strengthen sustainable practices and help companies to reach the goals proposed by triple bottom line. Furthermore, according to the results obtained by researchers of this area, the Circular Economy aims to explore the efficiency of using energy and materials, ensuring an economic growth, which is less dependent on natural resources, emphasizing, among others, to the redesign of processes that focus on the extension of products cycle of life.